Implementing Occupational Safety and Health Management System in a Forest Management Unit (FMU) X: A Financial Analysis - Ika Lestari; Efi Yuliati Yovi; Budi Kuncahyo (Jurnal Penelitian Kehutanan Wallacea, 2020)
Occupational safety and health (OSH) issues in the Indonesian forestry sector have not been addressed properly even though activities in this sector pose a high risk of OSH disorders. The standard instrument (applies on a national scale) to ensure OSH protection in each business units is the Sistem Manajemen K3 (SMK3, Government Regulation Numbered 50 Year 2012). At present, not many forest management units in Indonesia are willing to implement integrated SMK3, because of the assumption that SMK3 is a cost-centered activity. This study aims to present an overview of SMK3 implementation cost (for 64, 122, and 166 criteria) in a Forest Management Unit (FMU) X, as well as analyzing financial capacity of the FMU X to allocate sufficient funds for the SMK3 implementation. The results showed that the Acacia mangium plantation in the FMU X is a feasible business, indicated by the Net Present Value (NPV) of IDR377,690,545, Benefit-Cost Ratio (BCR) 3.96, and Internal Rate of Return (IRR) 25.02%. Further analysis shows that FMU X has good financial ability to support any cost required in implementating SMK3. It is the best for the FMU X to implement 166 criteria (advanced level) of SMK3 (at a cost of IDR704,598/ha/year, NPV ofIDR376,393,262, BCR 3.92, and IRR 24.75%).